Working with Mathematical Tools for Generating Complex Surfaces - Erkan Yazıcı, Yasemin; YAZICI, GÖKHAN (My University, 2012)
This paper presents the findings of a workshop conducted with the undergraduate students of architecture at the Istanbul Kultur University within the “Form and Geometry”course. The main aim of the workshop was to inform the students on the ways of working with mathematical tools for generating complex surfaces. Matlab was chosen as the mathematical tool for this workshop due to its ease of plotting curved surfaces. After a brief introduction to the user interface and plotting features of Matlab, students were given the task of generating a hyperbolic paraboloid surface. Afterwards, the students were asked to experiment with their model and observe the effect of the change in the parameters on the model geometry. Finally, the students were shown how to export the generated surface to a DXF file and asked to import the surface model to Autocad. The workshop was concluded with a group discussion on the views of participating students on using mathematical tools together with CAD tools to generate complex surfaces and the difficulties they have experienced throughout the exercise.
Keywords: Strength through Form; Hyperbolic Paraboloid Surfaces; Surface Generation; Parametric Design